Antimicrobial Activity of Naturally Occurring Phenols and Derivatives Against Biofilm and Planktonic Bacteria - Walsh, Danica J.; Livinghouse, Tom; Goeres, Darla M.; Mettler, Madelyn; Stewart, Philip S. (Frontiers in Chemistry, 2019)
Biofilm-forming bacteria present formidable challenges across diverse settings, and there is a need for new antimicrobial agents that are both environmentally acceptable and relatively potent against microorganisms in the biofilm state. The antimicrobial activity of three naturally occurring, low molecular weight, phenols and their derivatives were evaluated against planktonic and biofilm Staphylococcus epidermidis and Pseudomonas aeruginosa. The structure activity relationships of eugenol, thymol, carvacrol and their corresponding 2- and 4-allyl, 2-methallyl, and 2- and 4-n-propyl derivatives were evaluated. Allyl derivatives showed a consistent increased potency with both killing and inhibiting planktonic cells but they exhibited a decrease in potency against biofilms. This result underscores the importance of using biofilm assays to develop structure-activity relationships when the end target is biofilm.